Prognostic value of plasma interleukin 6 levels in severe traumatic brain injury - Afeefah Jamsheed; Suhail Sidiq; Abdul Qayoom Lone; Zaffar Amin (Asian Journal of Medical Sciences, 2023)
Background: Traumatic brain injury (TBI) results in a significant morbidity and mortality. Several inflammatory mediators are released after TBI. Some studies have shown inconclusive association between interleukin-6 (IL-6) and outcome following TBI. Aims and Objectives: The aim of the present study was to investigate the role of plasma IL-6 levels as a possible prognostic marker in patients with severe TBI. Materials and Methods: A total of 47 male patients with isolated severe TBI were included in a prospective observational study. Plasma IL-6 levels was measured at admission, 24 h and 48 h. Association of IL-6 levels with mortality and functional outcome were studied. The Glasgow outcome scale was used to assess functional outcomes. Results: Mean age was 44.4 years. Overall mortality of 42.6% was noted. Higher mortality was noted for patients beyond 50 years of age. Mean IL-6 levels at the time of admission was 306.285 pg/mL and 167.830 pg/mL at 24 h while 99.033 pg/mL at 48 h of admission Mean IL 6 levels were higher in patients with lower Glasgow coma scale (GCS), with a significant statistical association of GCS with IL-6 levels at admission and 24 h (P<0.001). 38 (80.85%) patients underwent surgical intervention. No statistical correlation was noted between IL-6 levels and mode of management. Significant IL-6 levels were seen in patients with worse clinical course at admission, 24 h and 48 h (P<0.0001). A level of 78 pg/mL was the appropriate cutoff to differentiate patient mortality as per receiver operating characteristic curve with Sensitivity of 1 and specificity of 0.8. Conclusion: IL-6 plasma concentrations are likely to be a useful parameter for assessing prognosis in severe TBI.